Demagnetisation of Social Security and Health Care for Migrants to the UK. Issue 2 (June 2016) - Harris, Neville
Over the past two decades, starting with the social security 'habitual residence' test, UK governments have maintained a consistent policy of restricting the access of migrants to welfare benefits and public health care. It has represented a response to increased levels of inward migration flow, including anticipated increases arising from enlarged European Union (EU) membership, and the supposed 'magnetic pull' of UK welfare and health care systems to migrants. Adjustment of the benefit rules affecting EU migrants, which has at times come very close to crossing lines of legality under EU law, has lately featured prominently in the UK's proposals to the EU over the terms of its Union membership. The article focuses on the policy changes and legal developments, including case law, across the areas of social assistance benefits, state retirement pensions and health care, and assesses their impact, seeking to analyse the changing position of residence as an issue in entitlement and its implications.